Effect of Gliotoxin on Human Polymorphonuclear Neutrophils. Issue 4 (1998) - Shah, D. T.; Jackman, S.; Engle, J.; Larsen, B.
Abstract : Objectives: Candida albicans is known to produce gliotoxin, which has several prominent biological effects, including immunosuppression. interference with host defenses may arise from the effects of this toxin on leukocyte structure and function. Methods: Flow cytometric analysis revealed that polymorphonuclear leukocytes (PMN) were more sensitive to gliotoxin than were mononuclear cells. Structural and various functional aspects of PMN exposed to gliotoxin were studied. Results: Gliotoxin at (1 μg/mL) did not affect the viability but did diminish PMN chemotaxis and reduced their ability to ingest particles. Other functional aberrations included decreased nitroblue tetrazolium dye reduction, decreased superoxide production, and release of lactoferrin suggesting by degranulation. Gliotoxin also affected the ability of PMN to kill Escherichia coli . Conclusions: This study suggests a previously unrecognized potential virulence factor of C. albicans that could contribute to persistence of yeast colonization or recurrence of symptomatic infection through diminished host resistance.